224k views
3 votes
How to solve for-6g + 36 = 12

User CaTourist
by
5.4k points

2 Answers

5 votes

Answer:

g= - 8

Explanation:

Simplifying

-6g + -36 = 12

Reorder the terms:

-36 + -6g = 12

Solving

-36 + -6g = 12

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '36' to each side of the equation.

-36 + 36 + -6g = 12 + 36

Combine like terms: -36 + 36 = 0

0 + -6g = 12 + 36

-6g = 12 + 36

Combine like terms: 12 + 36 = 48

-6g = 48

Divide each side by '-6'.

g = -8

Simplifying

g = -8

User Kruti Shukla
by
5.4k points
3 votes

Answer:

4

Explanation:

-6g+36=12

-6g=12-36

-6g=-24

6g=24

g=24/6

g=4

User Hakksor
by
5.2k points